Stories of strength: a systematic review of the use of narratives in character education of children - Valdez, Mohamad Alppy; Graaf, Anneke de; Barasa, Sandy; Das, Enny (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Character education has a significant role in instilling positive character strengths that help to shape a positive mind, a positive attitude, and positive behavior in children. Next to the commonly used didactic approaches, narrative interventions can be used to ‘package’ key moral messages about character strength in entertaining storylines. Unfortunately, empirical studies on the effectiveness of narrative methods for teaching character education to children is scattered across different disciplines. This review aimed to comprehensively describe the published studies, and identify the main elements used for children’s character education in the narratives. Eight databases of studies published between January 1980 and March 2018 were searched for narrative interventions that focused on character education aimed at children. The searches yielded seven studies with a great variety in outcome measures. Findings consistently suggest that narratives with positive approaches can generate honesty and kindness effectively in children. Employing a positively framed story, giving instructions, and encouraging children to explain the key story events half way and at the end of the story can especially produce preferable results in adopting the character strengths.